SUBSTITUSI RUMPUT GAJAH DENGAN TUMPI JAGUNG DAN KULIT KOPI TERHADAP PENAMPILAN SAPI PERANAKAN ONGOLE - Dicky Pamungkas; Eko Marhaeniyanto; Agustina Wea; Karolus Eduardus Suhana (Universitas Tribhuwana Tunggadewi, 2010)
The purpose of this research is to measure the substitution of pasture grass with corn tumpi and coffe pulp on feed intake, digestibility, feed intake digestibility, average daily gain , biological value and nitrogen balance of the Peranakan Ongole young cattle male. Twelve Peranakan Ongole (approximately 10-12 month old) with weight of 152 – 247 kg were use in this experiment, arrange in Random Block Complied Design with 3 treatment and 4 block. Composition of basal feed were corn tumpi dan coffe pulp (80:20) and the feed supplement were dry onggok and consentrate (50:50) with crude protein = 22%., The treatments applied were R0 (Elephant grass : Feed Supplement = 60% : 40%), R1 (Elephant grass : Basal feed : Feed Supplement = 30% : 30% : 40%), R2 (Basal feed : Feed Supplement = 60% : 40%). The variable observed were the dry matter intake (OMI), organic matter intake (DMO), crude protein intake (CPI), dry matter digestibility (DMD), organic matter digestibility (OMD), crude protein digestibility (CPD), dry matter intake digestibility (DMID), organic matter intake digestibility (OMID), crude protein intake digestibility (CPID), average daily gain (ADG), biological value and nitrogen balance. The result indicates that the average of feed intake (DMI, OMI, CPI), feed intake digestibility ((DMID, OMID, CPID) and biological value and nitrogen balance was very significantly different (P0.05). The usage of Ransum R2 tended to increased performance of the Peranakan Ongole young cattle male